Sacred Soujourn - Ivanova, Annie; Liou, Jawshing Arthur; Zhaoxing, Liu (Taipei Fine Arts Museum, 2014)
Text is in Chinese and English. Issued in conjunction with a 2014 exhibition of artwork by Taiwanese artist Liu Zhaoxing / Jawshing Arthur Liou (b. 1968), as he made a sacred sojourn into West Tibet. He presents for the first time, a complete installation series of videos from the country. With an illustrated essay by Annie Ivanova, a chronology and exhibitions history, and many illustrations of the mountains and the artwork woven amongst them. His work revolves around the themes of life, death and transcendence.
English; Chinese
Keywords: 21st century; N4390-5098 Visual Arts. Exhibitions; Tibet. Taiwan. China